Decreased mitochondrial respiration associates with frailty in community-dwelling older adults - Liabeuf, Gianella; Saguez, Rodrigo; Márquez, Carlos; Angel, Bárbara; Bravo-Sagua, Roberto; Albala, Cecilia (Frontiers in Cell and Developmental Biology, 2024)
Aging population has led to an increased prevalence of chronic and degenerative pathologies. A manifestation of unhealthy aging is frailty, a geriatric syndrome that implies a non-specific state of greater vulnerability. Currently, methods for frailty diagnosis are based exclusively on clinical observation.The aim of this study is to determine whether the bioenergetic capacity defined as mitochondrial oxygen consumption rate (OCR) of peripheral circulation mononuclear cells (PBMC) associates with the frailty phenotype in older adults and with their nutritional status. This is a cross-sectional analytic study of 58 participants 70 years and older, 18 frail and 40 non-frail adults, from the ALEXANDROS cohort study, previously described. Participants were characterized through sociodemographic and anthropometric assessments. Frail individuals displayed a higher frequency of osteoporosis and depression. The mean age of the participants was 80.2 ± 5.2 years, similar in both groups of men and women. Regarding the nutritional status defined as the body mass index, most non-frail individuals were normal or overweight, while frail participants were mostly overweight or obese. We observed that OCR was significantly decreased in frail men (p<0.01). Age was also associated with significant differences in oxygen consumption in frail patients, with lower oxygen consumption being observed in those over 80 years of age. Therefore, the use of PBMC can result in an accessible fingerprint that may identify initial stages of frailty in a minimally invasive way.